Предмет: Алгебра,
автор: Mika24862
(2а-3)(а+4)-(4а+2)(8а-6) это тема умножение многочленов помогите
Ответы
Автор ответа:
1
Ответ во вложении))))
Приложения:
Автор ответа:
2
(2a-3)(a+4)-(4a+2)(8a-6)=
=2a^2+8a-3a-12-(32a^2-24a+16a-12) =
=2a^2+8a-3a-12-(32a^2-8a-12)=
=2a^2+8a-3a-12-32a^2+8a+12=
=2a^2+8a-3a-32a^2+8a=-30a^2+13a
Ответ: -30a^2+13a
Похожие вопросы
Предмет: Математика,
автор: Мандресиа
Предмет: Русский язык,
автор: sakobyan80
Предмет: Алгебра,
автор: leehyuksoo
Предмет: Математика,
автор: Pon4ik001
Предмет: Математика,
автор: rita20065